The Feminine Presence in Youth Subcultures: the Art of Getting Visible - Weller, Wivian (Revista Estudos Feministas, 2005)
The omission of girls in the literature of youth (sub)cultures is evident. Are feminine groups, in fact, in a minority position in the hip hop movement or in other cultural expressions like the “galeras” or “gangs”? The present article interrogates the absence of research about girlcultures in the area of youth studies and also in the gender studies. Based on empirical research among black girls and girls of Turkish origin who belong to the hip hop movement in the cities of São Paulo and Berlin, respectively, the paper shows the effort of these girls in the achievement of power and recognition in this male dominated culture.